2019
DOI: 10.1093/jpepsy/jsz044
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Cascade from Prenatal Stress to Child Internalizing and Externalizing Problems

Abstract: Objective This study utilized a developmental cascade approach to test alternative theories about the underlying mechanisms behind the association of maternal prenatal stress and child psychopathology. The fetal programming hypothesis suggests that prenatal stress affects fetal structural and physiological systems responsible for individual differences in child temperament, which further increases risk for internalizing and externalizing problems. Interpersonal models of stress transmission s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 47 publications
3
45
0
Order By: Relevance
“…The link between prenatal maternal mental health problems, stress, and child negative emotionality persists throughout childhood and is associated with the development of children's internalizing problems (Davis & Sandman, 2012; Howland, Sandman, Glynn, Crippen, & Davis, 2016). A recent prospective study with close to 2,000 mother–child dyads measured maternal stress, anxiety, and depression both during pregnancy and postnatally and showed that prenatal distress predicted child negative emotionality at 3 years and internalizing problems at 5 years after covarying postnatal maternal mental health (Hentges, Graham, Plamondon, Tough, & Madigan, 2019). Prenatal maternal stress, anxiety, and depression also predicted elevated depressive symptoms in adolescence assessed by both maternal report and child self-report (Davis et al, 2019; O'Donnell et al, 2014).…”
Section: Fetal Programming: Maternal Prenatal Stress Predicts Child Mmentioning
confidence: 99%
“…The link between prenatal maternal mental health problems, stress, and child negative emotionality persists throughout childhood and is associated with the development of children's internalizing problems (Davis & Sandman, 2012; Howland, Sandman, Glynn, Crippen, & Davis, 2016). A recent prospective study with close to 2,000 mother–child dyads measured maternal stress, anxiety, and depression both during pregnancy and postnatally and showed that prenatal distress predicted child negative emotionality at 3 years and internalizing problems at 5 years after covarying postnatal maternal mental health (Hentges, Graham, Plamondon, Tough, & Madigan, 2019). Prenatal maternal stress, anxiety, and depression also predicted elevated depressive symptoms in adolescence assessed by both maternal report and child self-report (Davis et al, 2019; O'Donnell et al, 2014).…”
Section: Fetal Programming: Maternal Prenatal Stress Predicts Child Mmentioning
confidence: 99%
“…However, co‐occurring and/or persistent RPs can increase the risk of internalising and externalising symptoms and mental disorders across childhood and adolescence (Bilgin et al., ; Cook et al., ; Hemmi, Wolke, & Schneider, ; Hyde, O'Callaghan, Bor, Williams, & Najman, ; Toffol et al., ; Winsper & Wolke, ). The cascade model of development describes how early risk predictors can cumulatively influence maladaptive outcomes over time (Hentges, Graham, Plamondon, Tough, & Madigan, ). The ‘cascade’ represents the extent to which differences in emotion or behaviour maximally affect the next most proximate phase of development, which in turn affects the following stage, and so on (Hyde et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly although our cross-fostered sample size was small, the notable behavioral consequences were identical across both groups, demonstrating the independence Prior research suggests that prenatal stress is a risk factor for behavioral dysregulation and problematic outcomes in animal and human health (Schneider et al, 1992(Schneider et al, , 2002Coe et al, 2003;Gutteling et al, 2005;Ruiz and Avant, 2005;Pryce et al, 2011). In studies conducted on human children, prenatal stress has been linked with both internalizing and externalizing behavior dysregulation (Betts et al, 2014;MacKinnon et al, 2018;Hentges et al, 2019). Moreover, multiple studies have shown a link between prenatal stress and signs of internalizing behavior at an early age.…”
Section: Discussionmentioning
confidence: 74%
“…The consequences of prenatal stress on infant development are diverse (Clarke and Schneider, 1993;Gutteling et al, 2005;DiPietro et al, 2006;Hartman et al, 2018). Some studies have shown prenatal stress leads to internalizing outcomes (negative affect, poor soothability, anxiety; Gutteling et al, 2005;Hentges et al, 2019), some to externalizing outcomes (impulsivity, poor self control; Gutteling et al, 2005;Betts et al, 2014;MacKinnon et al, 2018), and still others, to resilient outcomes (advanced cognitive development and stress resistance; Fujioka et al, 2001;DiPietro et al, 2006). We observed that offspring of mothers that were relocated for an average of 9 days over an average of 1.5 relocations during pregnancy were more active, confident, and willing to engage with novelty, and exhibited lower post-stress cortisol during a moderately stressful social separation at 90-120 days of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation